Instructional Analysis of Civilization Education Lesson Plan’s for Class V SDN Pandanwangi I Malang - Huda, Misbahul; Mubaidilla, Irfa'i Alfian; Ainiyah, Ziana Dhurrotul (Journal of Asian Primary Education (JoAPE), 2024)
The purpose of this study was to determine how teachers translate KD into indicators of competency achievement in the preparation of lesson plans. For this purpose, an instructional analysis of the Civics lesson plan for grade V elementary school was conducted. The subject of the research was the teacher of class V A SDN Pandanwangi I Malang. The number of lesson plans analyzed was 10 lesson plans. The main focus of the research problem is limited to the instructional analysis of the lesson plans developed by the research subjects, namely the translation of basic competencies into indicators. Further instructional analysis focused on lesson plans in which there were instructional errors in the translation of KD into indicators of competency achievement. The results showed that in the elaboration of KD into indicators of competency achievement in the ten lesson plans analyzed, it was found that teachers had elaborated KD into indicators well in the preparation of Civics lesson plans for grade V elementary school. The KD of Civics subject in Grade V consists of operational KD formulation and non-operational KD formulation. Except for the operational KD formulation, there are instructional analysis errors made by teachers in translating KD into indicators, namely in the formulation of non-operational KD. The instructional error in question is that the teacher formulates indicators that are not detailed, not comprehensive, and not systematic. This finding is in 3 KD, namely KD 2.2, KD 2.3, and KD 3.2.